Muslims` attitude towards divorce: the problem of fiqh postulate - Mahmud , Mek Wok (2010)
Divorce in its variant forms whether initiated by a husband or a wife ideally should be controlled within the minimum limit as anticipated by the socio-religious requirements of Islam .The reason being that the Prophet has vociferously condemned its wanton use by both women and men. Nevertheless, in our age marriage break- ups ending in divorces have become a worrying phenomenon the world over, including Malaysia. . To remedy the situation, legislative reforms of the Muslim laws have been a regular exercise. However, in our view, for such reforms to succeed ,we need to address the basic jurisprudential postulates that have shaped its laws and orientated public outlook/attitude towards practicing it. The bottom line, therefore is as to how Muslims perceive divorce and its procedures ,as formulated by the dominant schools of legal thought.The most widely held opinion among people is that they can practice divorce even if it contradicts the set procedures of the Qur`an .Simply because a certain school of legal thought validates it.This kind of naïve approach to Islamic law as articulated by many law books on divorce ,being a replica of the larger problem of taqlid, has seriously hampered the success of reform attempts in our time .Accordingly, in this paper , we try to take the readers ``back to basics`` with the prime aim of enlightening them about some pertinent jurisprudential postulates that surround the dissolution of marriage .To this end ,the paper covers a brief overview of divorce ,then it proceeds to address its jurisprudential postulates in terms of Shari `ah value and its procedure so as to identify the most Shari`ah consistent view from among the variety of juristic interpretation.